2018
DOI: 10.1186/s10397-018-1045-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pelvic pain and the role of exploratory laparoscopy as diagnostic and therapeutic tool: a retrospective observational study

Abstract: Background: Forty percent of exploratory laparoscopies are performed for chronic pelvic pain (CPP). However, a final diagnosis is still unreported in 35% of the patients. We decided to evaluate the identification of pathological lesions and the improvement of painful symptoms in patients with CPP and normal physical examination and imaging and who are scheduled for exploratory laparoscopy. The prospective study was designed in a tertiary referral center for endometriosis. Forty-eight patients complaining of CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
10
2
Order By: Relevance
“…The commonest surgical intervention was cystectomy (40.7%), this goes with our finding that most of the pathology was ovarian cyst. This disagree with what found by Brichant, G., et al [9] reported performance of cystectomy in (17%) of the patients ,…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The commonest surgical intervention was cystectomy (40.7%), this goes with our finding that most of the pathology was ovarian cyst. This disagree with what found by Brichant, G., et al [9] reported performance of cystectomy in (17%) of the patients ,…”
Section: Discussioncontrasting
confidence: 95%
“…)% It is possible that more than one lesion could have been found in a patient and so more than one surgical procedure would then be carried out. [9] In all cases but one, adhesiolysis has been always associated with another surgical procedure. In 66% of the patients undergoing excision of USLs, another procedure was performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have stressed upon the duration, its pattern and the location of pain to describe CPP. 1,2 Howard gave a most satisfactory definition which state that non-menstrual pain which last for at least 3 months of duration, localizes to the anatomic pelvis and its extent that can cause functional disability and require medical or surgical treatment is called CPP. 3 Adhesions describe the connections between opposing serosal and/or nonserosal surfaces of internal organs and the abdominal wall.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, multifactorial, chronic pelvic pain (CPP) is a common complaint in woman of childbearing age. In such case, laparoscopy as a diagnostic tool, allows also to treat certain pathologies related to CPP, like endometriosis (presence of uterine endometrial tissue outside of the normal location) [1]. Complete surgical excision of endometriosis has been proved as an effective treatment to relieve pain and improve quality of life [2].…”
Section: Introductionmentioning
confidence: 99%